Alley connecting Walkeshwar Road to Banganga Tank - Ghosh, Ayan (2023)
The neighborhood of Walkeshwar is one of the few places in Mumbai that has a marked elevation due to its location on Malabar Hill. There are several theories about how the hill got its name after the Malabar coastline in modern Kerala. One theory is the hill being used as a refuge by pirates from the Malabar coast who preyed upon European shipping. Another theory is the hill got named after pilgrims from the Malabar coast who used to visit the original Walkeshwar Temple and the Shri Gundi sacred rock, both of which were later destroyed, thus ending the long-established practice.